Since x+ 3 is a factor of x2-bx-12 ,P(minus3)=0 therefore= (minus3)whole square minus b× minus3 minus 12 =9+3b minus 12 =minus3. 3b=minus 3 b. minus3/minus 3 b=1 hence proved
Since x+ 3 is a factor of x2-bx-12 ,P(minus3)=0 therefore= (minus3)whole square minus b× minus3 minus 12 =9+3b minus 12 =minus3. 3b=minus 3 b. minus3/minus 3 b=1 hence proved
Track your progress, build streaks, highlight & save important lessons and more!
Since x+ 3 is a factor of x2-bx-12 ,P(minus3)=0 therefore= (minus3)whole square minus b× minus3 minus 12 =9+3b minus 12 =minus3. 3b=minus 3 b. minus3/minus 3 b=1 hence proved